Designing variable sampling plans based on lifetime performance index under failure censoring reliability tests. Issue Volume 32:Issues 3(2020) (2nd July 2020) - Rasay, Hasan; Naderkhani, Farnoosh; Golmohammadi, Amir Mohammad
Abstract: In this paper, we develop two novel variable reliability acceptance sampling (RAS) plans referred to repetitive group sampling (RGS) and resubmitted sampling (RS), for failure censoring reliability tests by considering information obtained during life test using lifetime performance index (LPI) under Weibull distribution assumption for item lifetime. Performances of the proposed plans are compared with the single sampling (SS) plan through real case studies which show the great performances of proposed plans in terms of minimization of the average failure number of tested items.